The World of Open Data Concepts, Methods, Tools and Experiences - Charalabidis, Yannis (Public Administration and Information Technology,, 2018)
This book discusses the latest developments in the field of open data. The opening of data by public organizations has the potential to improve the public sector, inspire business innovation, and establish transparency. With this potential comes unique challenges; these developments impact the operation of governments as well as their relationship with private sector enterprises and society. Changes at the technical, organizational, managerial, and political level are taking place, which, in turn, impact policy-making and traditional institutional structures. This book contributes to the systematic analysis and publication of cutting-edge methods, tools, and approaches for more efficient data sharing policies, practices, and further research. Topics discussed include an introduction to open data, the open data landscape, the open data life cycle, open data policies, organizational issues, interoperability, infrastructure, business models, open data portal evaluation, and research directions, best practices, and guidelines. Written to address different perspectives, this book will be of equal interest to students and researchers, ICT industry staff, practitioners, policy makers and public servants. .